2000
DOI: 10.1046/j.1440-172x.2000.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

The context of care: Issues of power and control between patients and community mental health nurses

Abstract: Issues of power and control are inevitably linked to the nurse–patient relationship within mental health settings. This paper discusses power relations between nurses and patients within the context of the home visit as an important component of the provision of care to patients living with enduring mental illness. An interpretive ethnographic account was adopted to explore how nurses and patients negotiated issues of power and control with respect to the specific responsibilities associated with community men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…While there is a body of work about the nature of mental health care and the complexity of nurses’ roles and attitudes to restrictive measures (Bowers et al . , ; Muir‐Cochrane ; Muir‐Cochrane & Duxbury ; Van Der Merwe et al . ), this is the first time nurses’ concerns have been articulated as fear and blame about the potential elimination of containment measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a body of work about the nature of mental health care and the complexity of nurses’ roles and attitudes to restrictive measures (Bowers et al . , ; Muir‐Cochrane ; Muir‐Cochrane & Duxbury ; Van Der Merwe et al . ), this is the first time nurses’ concerns have been articulated as fear and blame about the potential elimination of containment measures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Slemon et al (2017) suggest that the risk management culture itself gives rise to and legitimizes restrictive practices. While there is a body of work about the nature of mental health care and the complexity of nurses' roles and attitudes to restrictive measures (Bowers et al 2010(Bowers et al , 2014Muir-Cochrane 2000;Muir-Cochrane & Duxbury 2017;Van Der Merwe et al 2013), this is the first time nurses' concerns have been articulated as fear and blame about the potential elimination of containment measures.…”
Section: Discussionmentioning
confidence: 99%
“…The main theme of having equal footing with the client resonates with the literature. Subthemes include respecting the client's will, developing an equal relationship, reflecting to increase self‐awareness, and trusting the client (Magnusson & Lutzen 1999; Muir‐Cochrane 2000; O'Brien 2000). Achieving positive attitudes is essential for home‐visit nurses to effectively help clients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Hammarström (1997) proposed adjustment, exit, and protest as patient power strategies, although these suggestions are not based on an empirical study. Muir-Cochrane (2000) found that patients controlled the encounter with community mental health nurses by, among other things, using noncommunicative or aggressive behavior. Johansson, Hamberg, Lindgren, and Westman (1996) have reported that patients with fibromyalgia sometimes use persuasion in their interaction with health care providers.…”
Section: Discussionmentioning
confidence: 99%